Children's materials science practices before, during, and after a design-based science learning experience - Wendell, Kristen B. (Tufts Archival Research Center, 2014)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Math, Science, Technology, and Engineering Education. Abstract: Materials science, which entails the practices of selecting, testing, and characterizing materials, is an important discipline within the study of matter. This paper examines how third grade students' materials science performance changes over the course of instruction based on an engineering design challenge. I conducted a case study of nine students who participated in engineering design-based science instruction with the goal of constructing a stable, quiet, thermally comfortable model house. The learning outcome of materials science practices was assessed by clinical interviews conducted before and after the instruction, and the learning process was assessed by students' workbooks completed during the instruction. The interviews included two materials selection tasks for designing a sturdy stepstool and an insulated pet habitat. Results indicate that (1) students significantly improved on both materials selection tasks, (2) their gains were significantly positively associated with the degree of completion of their workbooks, and (3) students who were highly engaged with the workbook's reflective record-keeping tasks showed the greatest improvement on the interviews. These findings suggest the important role workbooks can play in facilitating elementary students' learning of science through authentic activity such as engineering design.